Corpus der römischen Bleibarren. Historisch-archäologische und naturwissenschaftliche Untersuchungen zur Bleiproduktion im Römischen Reich. Die Arbeiten des Jahres 2018 - Rothenhöfer, Peter (e-Forschungsberichte des DAI, 2018)
This interdisciplinary project aims to gain in-depth insights into ancient economic history in the field of metal extraction and raw material distribution by combining epigraphic, archaeological, and archaeometallurgical methods. Lead ingots are particulary suitable as objects of investigation. On the one hand because of the huge number of ingots, on the other hand because of the possibility to trace the origin of the lead by lead isotope analysis. Data of more than 2600 ingots were collected within the first years of this project, most of them by autopsy in more than 15 countries. In 2018, the publication of both the “Corpus of Roman Lead Ingots” and various articles are in preparation.